The Influence of Marketing Communication and Service Quality on Customer Loyalty Using Tabungan Simpeda Products at PT Bank Pembangunan Daerah Kalimantan Barat Main Branch Through Satisfaction as an Intervening Variable - Diki Wahyudi; Ananda Archie (Electronic Journal of Education, Social Economics and Technology, 2025)
This study aims to analyze the influence of marketing communication and service quality on customer loyalty for Tabungan Simpeda customers at PT Bank Pembangunan Daerah Kalimantan Barat Main Branch, with satisfaction as an intervening variable. This research uses an associative quantitative approach with a sample of 100 active customers selected through purposive sampling. Data were collected through observation, questionnaires, and secondary documents, then analyzed using the Partial Least Square - Structural Equation Modeling (PLS-SEM) method with SmartPLS. The direct effect test shows that marketing communication and service quality have a direct and significant effect on satisfaction and loyalty. In addition, satisfaction has a direct effect on loyalty. The F-Square test shows that the contribution of marketing communication to loyalty is 0.354 (strong category), service quality to loyalty is 0.329 (moderate), and satisfaction to loyalty is 0.211 (moderate). The indirect effect test shows that satisfaction successfully mediates the influence of marketing communication and service quality on loyalty. In conclusion, marketing communication and service quality are proven to be key factors in increasing satisfaction, which ultimately strengthens customer loyalty. The practical implication of this study highlights the importance of consistent communication strategies and excellent service quality to maintain customer loyalty and support the competitiveness of Bank Kalbar as a regional bank. Future research is recommended to add other variables such as trust or brand image and to expand the sample to make the results more generalizable.